Development of Teaching and Learning Module for Basic Electrical and Electronic Course - Ab Rahman, Azmanirah; Mustadza, Nabilah; Mohamed Yusof, Anizam (Research and Innovation in Technical and Vocational Education and Training, 2021)
Students taking the electrical and electronics course will typically take basic subjects that include sub-topic as well as Norton, Thevenin, Mesh, Nodal and Superposition. However, the content of this topic is difficult for students to understand because it involves complex calculations. Therefore, teaching and learning modules for Basic Electrical and Electronics have been developed. To conduct the study more systematically, this module was developed based on the module development process by Sharifah Alwiah Alsagoff (1981). As a result, the development of this module was successfully implemented. The modules produced meet the criteria that have been set and validated by experts according to the suitability of the design and content aspect